Exercise-heat acclimation in young and older trained cyclists - Best, S.; Thompson, M.; Caillaud, C.; Holvik, L.; Fatseas, G.; Tammam, A. (Journal of Science and Medicine in Sport, 2014)
Objectives: The purpose of this study was to investigate the effect of age on the capacity to acclimatise to exercise-heat stress. This study hypothesised that age would not affect body temperature and heat loss effector responses to short-term exercise-heat acclimation in trained subjects. Design:Seven young subjects (19-32 years) were matched with 7 older subjects (50-63 years). Subjects were highly trained but not specifically heat acclimated when they exercised for 60 min at 70%VO2max in hot-dry (35 °C, 40%RH) and thermoneutral (20 °C, 40%RH) conditions, pre and post 6 days of exercise-heat acclimation (70%VO2max, 35 °C, 40%RH). Methods:Rectal temperature (Tr), skin temperature (Tsk), heart rate (HR), cutaneous vascular conductance (CVC) and whole body sweat loss (Msw) were measured during each testing session and Tr and HR were measured during each acclimation session. Results: Tr, Tsk, %HRmax, CVC and Msw were similar across age groups both pre and post heat acclimation. Following heat acclimation relative decreases and increases in Tr and Msw, respectively, were similar in both subject groups. There was a significant reduction in heart rate (%HRmax) and increase in final CVC following the acclimation programme in the young group (all p < 0.05) but not the older group. Conclusions: When comparing young and older well trained adults we found age affected the cardiovascular adaptation but not body temperature or whole body sweat loss to exercise-heat acclimation. These data suggest age does not affect the capacity to acclimatise to exercise-heat stress in highly trained adults undergoing short-term heat acclimation.